Senescence in Monocytes Facilitates Dengue Virus Infection by Increasing Infectivity - Hsieh, Tzu-Han; Tsai, Tsung-Ting; Chen, Chia-Ling; Shen, Ting-Jing; Jhan, Ming-Kai; Tseng, Po-Chun; Lin, Chiou-Feng (Frontiers in Cellular and Infection Microbiology, 2020)
Aging and chronic condition increase the incidence of dengue virus (DENV) infection, generally through a mechanism involving immunosenescence; however, the alternative effects of cellular senescence, which alters cell susceptibility to viral infection, remain unknown. Human monocytic THP-1 cells (ATCC TIB-202) treated with D-galactose to induce cellular senescence were susceptible to DENV infection. These senescent cells showed increased viral entry/binding, gene/protein expression, and dsRNA replication. The use of a replicon system showed that pharmacologically induced senescence did not enhance the effects on viral protein translation. By examining viral receptor expression, we found increased expression of CD209 (DC-SIGN) in the senescent cells. Interleukin (IL)-10 was aberrantly produced at high levels by the senescent cells, and the expression of the DENV receptor DC-SIGN was increased in these senescent cells, partially via IL-10-mediated regulation of the JAK2-STAT3 signaling pathway. The results demonstrate that a senescent phenotype facilitates DENV infection, probably by increasing DC-SIGN expression.